2021
DOI: 10.1002/ppap.202100078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen content in films on the etching of LPCVD and PECVD SiN films using CF4/H2 plasma at different substrate temperatures

Abstract: The dependences of etching characteristics on substrate temperature (Ts, from –20 to 50°C) of the plasma‐enhanced chemical vapor deposition (PECVD) SiN films (PE‐SiN) and low‐pressure chemical vapor deposition (LPCVD) SiN films (LP‐SiN) with CF4/H2 plasma were investigated. The Fourier‐transform infrared spectroscopy shows that both film types were N–H bond‐rich films, but in different hydrogen contents (PE‐SiN 22.7 at% and LP‐SiN 3.8 at%) from the Rutherford backscattering spectroscopy analyses. A higher hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…11,30,32 Unlike the SiN ALE using CH 3 F/Ar, which presented a decrease in EPC with respect to etch cycle, in this work, the increase in EPC after four cycles is likely due to the reason that the H 2 plasma in the etching step can incorporate with residual carbon, resulting in the formation of HCN by-products with the N in SiN. 47 Furthermore, the ALE fluctuation also introduces difficulties in error analysis of EPC, as it strongly depends on the parameters used in the deposition half-cycle. The error bars in Figures 7 and 8 represent the variation of EPC before significant ALE fluctuation occurred.…”
Section: Characterization Of Hfc Films Formed By the Cf 4 /H 2 Plasmasmentioning
confidence: 69%
See 1 more Smart Citation
“…11,30,32 Unlike the SiN ALE using CH 3 F/Ar, which presented a decrease in EPC with respect to etch cycle, in this work, the increase in EPC after four cycles is likely due to the reason that the H 2 plasma in the etching step can incorporate with residual carbon, resulting in the formation of HCN by-products with the N in SiN. 47 Furthermore, the ALE fluctuation also introduces difficulties in error analysis of EPC, as it strongly depends on the parameters used in the deposition half-cycle. The error bars in Figures 7 and 8 represent the variation of EPC before significant ALE fluctuation occurred.…”
Section: Characterization Of Hfc Films Formed By the Cf 4 /H 2 Plasmasmentioning
confidence: 69%
“…This is because the C–C bonds in the HFC polymer are difficult to be removed via physical ion bombardment with low energy . Hence, various approaches have been attempted, such as using additional ashing processes or adding O 2 into gas mixtures, to inhibit the formation of residual carbon. ,, Unlike the SiN ALE using CH 3 F/Ar, which presented a decrease in EPC with respect to etch cycle, in this work, the increase in EPC after four cycles is likely due to the reason that the H 2 plasma in the etching step can incorporate with residual carbon, resulting in the formation of HCN by-products with the N in SiN . Furthermore, the ALE fluctuation also introduces difficulties in error analysis of EPC, as it strongly depends on the parameters used in the deposition half-cycle.…”
Section: Resultsmentioning
confidence: 89%
“…On etching of the PECVD-prepared SiN films by the SF 6 /O 2 plasma, a decrease in ER of only ~10% was reported when the T s was cooled to down to −30 • C [20]. Recently, we reported that the T s affected ER more significantly in the PECVD-prepared SiN film than in the LPCVD-prepared film, because of the much greater hydrogen content inside the PECVD-prepared films [21]. In addition, the effects of T s on ERs in two bonding types (Si-H bond rich or N-H bond rich) of the PECVD-prepared SiN films were also addressed [22].…”
Section: Introductionmentioning
confidence: 97%
“…It has also been reported that high SiN/SiO 2 selectivity can be achieved using gas mixtures such as NF 3 /O 2 or CF 4 /N 2 /O 2 plasmas, which is attributed to the influence of NO radicals. , The addition of hydrogen to fluorocarbon gas, leading to the generation of CH x F y ions, can be used to enhance the etch rate (ER) and/or selectivity of SiN/SiO 2 or SiN/Si. Special hydrofluorocarbon gases have been used to achieve high etch selectivity for SiN over SiO 2 and Si. Additionally, the dependence of selectivities between Si-based materials on substrate temperature has recently been investigated by various research groups. , In hydrogen-contained fluorocarbon plasmas, the formation of hydrogen fluoride (HF) is anticipated to have a detrimental effect on etching for Si-based materials, as it tends to scavenge F radicals . In the mechanism of SiN etching, the H also reacts with N and CF x species, resulting in the formation of HCN as a byproduct, which helps to reduce the FC polymerization and facilitates the progress of SiN etching. , Based on the experimental and simulation results, it has been reported that HF molecules appear to play an important role in the selective etching of SiN over SiO 2 in NF 3 /N 2 /O 2 /H 2 remote plasmas , On the other hand, recently, there have been investigations into the selective etching of SiO 2 over SiN or Si using an HF vaper, employing both computational simulations and experimental approaches. , …”
Section: Introductionmentioning
confidence: 99%
“…16 In the mechanism of SiN etching, the H also reacts with N and CF x species, resulting in the formation of HCN as a byproduct, which helps to reduce the FC polymerization and facilitates the progress of SiN etching. 17,18 Based on the experimental and simulation results, it has been reported that HF molecules appear to play an important role in the selective etching of SiN over SiO 2 in NF 3 /N 2 /O 2 /H 2 remote plasmas 19,20 On the other hand, recently, there have been investigations into the selective etching of SiO 2 over SiN or Si using an HF vaper, employing both computational simulations and experimental approaches. 21,22 In the present work, CF 4 and HF plasma discharges diluted with H 2 were utilized to etch the SiN films prepared by plasmaenhanced chemical vapor deposition (PECVD).…”
Section: ■ Introductionmentioning
confidence: 99%